Hubungan Pengetahuan Dengan Kepatuhan Pelaksanaan Senam Hipertensi Pada Penderita Darah Tinggi Di Wilayah Puskesmas Punggelan 2 - Fitriyatun, Elista Fitriyatun; Nutrisia Nu’im Haiya; Abrori; Moch Aspihan (An-Najat, 2025)
Hypertension is a chronic disease that requires good management, one of which is through hypertension exercises. Sufficient knowledge can support compliance in carrying out regular hypertension exercises. This research used a cross-sectional design with purposive sampling technique, involving 144 respondents. Data were analyzed using univariate and bivariate tests with Spearman correlation. The majority of respondents were at least 50 years old and female (50.7%).  As many as 49.3% of respondents had a poor level of knowledge, and 47.9% were not compliant in carrying out hypertension exercises. The results of statistical tests show that there is a significant relationship between knowledge and adherence to hypertension exercise. There is a significant relationship between the level of knowledge and compliance with implementing hypertension exercises in high blood pressure sufferers at the Punggelan 2 Community Health Center.